Collapse resistance of multi-storey steel frame structures: Evaluation method based on member resistance. (1st June 2022) - Zhong, Wei-hui; Zheng, Yu-hui; Meng, Bao; Tan, Zheng; Duan, Shi-chao
Abstract: As the interaction of structural members and the type of beam-to-column connections significantly influence the collapse resistance of steel frame structures, there are limitations in using the existing theoretical models to calculate the resistance of multi-story steel frame structures with different structural parameters. The collapse resistance of multi-storey frame structures can be calculated using member resistance based on determining the inter-story constraints and the law of mutual influence of inter-story internal forces. In this paper, the resistance of structural members during the small and large deformation stage is discussed based on the coupling relationship between the bending moment and axial force developed in members. The theoretical analysis showed that the evolution of internal force multi-storey frames was reflected in the inter-story differences of flexural resistance and axial forces in the small and large deformation stages, respectively. Thus, a resistance calculation method suitable for steel frame structures with different connections was proposed based on member resistance. Finally, the rationality of the theoretical method was verified through a multi-scale model. The theoretical calculations showed a significant agreement with the numerical results. Highlights: A theoretical method for collapse resistance analysis was proposed. The resistance of members during different deformation stage is discussed. An approach calculating inter-story constraints was proposed. The interaction and limit state of structural members are considered.